2013
DOI: 10.1007/s10151-013-1071-2
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic extralevator abdominoperineal excision of the rectum: short-term outcomes of a prospective case series

Abstract: Laparoscopic extralevator abdominoperineal excision can be safely performed without compromising short-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 32 publications
0
14
1
Order By: Relevance
“…Kipling et al [43] have reported a shorter hospital stay (7 days) than our study. Patients in their study followed an enhanced recovery programme and they included only laparoscopic procedures.…”
Section: Discussioncontrasting
confidence: 60%
“…Kipling et al [43] have reported a shorter hospital stay (7 days) than our study. Patients in their study followed an enhanced recovery programme and they included only laparoscopic procedures.…”
Section: Discussioncontrasting
confidence: 60%
“…16 16,24,27,39 the proportion of patients receiving radiotherapy ranged from 43% to 100%, and an omental plasty was used in 28% (n = 36) and described in 2 studies. 16 16,24,27,39 the proportion of patients receiving radiotherapy ranged from 43% to 100%, and an omental plasty was used in 28% (n = 36) and described in 2 studies.…”
Section: Perineal Wound Problems and Perineal Hernia After Biologicalmentioning
confidence: 99%
“…5860 In the era of laparoscopic surgery, the routine use of rectus abdominis flaps seems counterintuitive and is likely to lead to longer-term abdominal wall problems. The acceptable outcomes associated with porcine dermal meshes offer an alternative solution, particularly if associated with cost savings due to shorter operating times, no need for plastic surgical input, and a reduction in hospital length of stay 61.…”
Section: Perineal Reconstruction Following Extralevator (El) Abdominomentioning
confidence: 99%